Investigation of Entanglement in the Moshinsky Atom - Hamdollah Salehi; Mehrzad Ashrafpour; Hamide Arimashi (فیزیک کاربردی ایران, 2023)
One of the most critical aspects of studying entanglement states is quantifying the degree of entanglement. One of the entanglement measures for pure states is Van- Neumann entropy, which is why Van-Neumann entropy is also called entanglement entropy. In this work, to calculate the entanglement of a three-particle atom called the Moshinsky atom; first, the reduced density matrix was calculated and then using the coordinates of the three particles in the lithium atom, the entropy entanglement was calculated. We obtained the entropy of entanglement in terms of the frequency parameter related to the external coordinate field.